(untitled) (Gaceta Técnica, 2022)
The comparative analysis of the E.030 2003, 2016 and 2018 seismic design standards is presented, in a study of structures using the portal system for office use in the city of Lima, it focuses on the comparison of vibration periods, percentage of participatory mass, design spectrum, mezzanine distortion, static basal shear force, dynamic and maximum design forces (bending, shear and axial moment), modeled using Etabs 17 software. The regular structure presented variation of 12.50% of static shear and 12.20% for the dynamic analysis according to the 2003 standard compared to 2016 - 2018 and the irregular structure varies by 50% according to the 2003 standard compared to 2016, also a variation of -16.67 % between the 2016 and 2018 norm directly affected by the irregularity changes. The 2018 standard has intermediate results considering modal periods for both structures through static and dynamic analysis.